Peripapillary retinal nerve fiber layer thickness in patients with unilateral retinal vein occlusion - Jayoung Ahn (Nature Portfolio, 2021)
Abstract This study evaluated longitudinal changes in peripapillary retinal nerve fiber layer (pRNFL) thickness in eyes affected with branch and central retinal vein occlusion (BRVO and CRVO, respectively) and fellow eyes. This retrospective case–control study included patients with newly diagnosed unilateral BRVO (46 patients) or unilateral CRVO (27 patients). The control group included 48 patients without abnormal findings on the fundus examination. Global and all-sector pRNFL thicknesses were greater in eyes with BRVO and CRVO than in fellow eyes at baseline; however, at 24 months, this difference remained only in the temporal sector of eyes affected with CRVO. Although the global pRNFL thicknesses of the fellow eyes in the BRVO and CRVO groups decreased significantly at 24 months compared to baseline (p = 0.001 and p = 0.011, respectively), there was no significant difference in the normal control group (p = 0.824). The global, inferior temporal, and inferior nasal pRNFL thicknesses at 12 and 24 months were significantly lower in the fellow eyes of the CRVO group than in those of the BRVO and normal control groups. The fellow eyes of patients with BRVO and CRVO suffered a significant reduction in pRNFL thickness compared to normal controls, indicating that they are susceptible to pRNFL damage.